Effectiveness and safety of Korean medicine treatment based on the clinical practice guidelines in patients with acute peripheral facial palsy: A protocol for a multicenter, prospective, observational study. Issue 27 (8th July 2022) - Lim, Hyewon; Lee, Yoonji; Lee, Suji; Kim, Yong-Suk
Abstract : Introduction: Peripheral facial palsy (PFP) results in weakness or paralysis of the affected side of the face. In Korea, there is a high demand for Korean medicine treatment for PFP. The clinical practice guidelines (CPGs) of Korean medicine for facial palsy were developed; however, there remains insufficient evidence to support the effectiveness and safety of Korean medicine treatment. Thus, this study aimed to evaluate the effectiveness and safety of Korean medicine treatment based on the CPGs in patients with acute PFP. Methods: This is a multicenter, prospective, observational study. The participants will be recruited from one Korean medicine hospital and eight Korean medicine clinics. The participants will receive Korean medicine treatments based on the CPGs, fill in survey questionnaires, and undergo electrophysiologic testing. The changes in House-Brackmann (H-B) grade, movement of the lip and eye, symptoms related to or accompanied by facial palsy, Facial Disability Index, EuroQol 5-dimension 5-level (EQ-5D-5L), and EuroQol Visual Analogue Scale (EQ-VAS), and the results of electromyography (EMG), electroneurography (ENoG), and Blink Reflex test will be analyzed. For the safety analysis, adverse events will be recorded, and for the feasibility analysis, the results of the Was It Worth It questionnaire will be assessed. Conclusion: We expect to draw real-world clinical data on the effectiveness and safety of Korean medicine treatment based on the CPGs in patients with acute PFP from this study. It would be the basis for complementing and improving the CPGs and provide the basis of clinical and policy decision-making. Trial registration: This study was approved by the Institutional Review Board of Kyung Hee University Korean Medicine Hospital (2021-06-005-001), and registered with the Korean Clinical Trial Registry (CRIS), Republic of Korea (KCT0006562).